2018
DOI: 10.1111/odi.12908
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of macrophage viability, differentiation, and function by bisphosphonates

Abstract: BPs directly acted on macrophage by reducing macrophage survival, inducing morphological alterations, impairing differentiation from monocytes to macrophages, and affecting macrophage function at both mRNA and activity levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 36 publications
0
28
0
2
Order By: Relevance
“…The family of bisphosphonates is used in the treatment of osteoporosis, certain bone tumors, and bone metastasis. Bisphosphonates are capable of reducing the number and impairing function of monocytes and specialized macrophages ( 66 ). Treatment with a member of this family, clodronate disodium, has shown effectiveness in animal models of pulmonary coronavirus infections ( 67 ), but the impact of clodronate disodium on the microglia can also make animals more susceptible to neural damage in a coronavirus encephalitis model ( 68 ).…”
Section: Systemic Inflammatory Response Induced By Lung Inflammationmentioning
confidence: 99%
“…The family of bisphosphonates is used in the treatment of osteoporosis, certain bone tumors, and bone metastasis. Bisphosphonates are capable of reducing the number and impairing function of monocytes and specialized macrophages ( 66 ). Treatment with a member of this family, clodronate disodium, has shown effectiveness in animal models of pulmonary coronavirus infections ( 67 ), but the impact of clodronate disodium on the microglia can also make animals more susceptible to neural damage in a coronavirus encephalitis model ( 68 ).…”
Section: Systemic Inflammatory Response Induced By Lung Inflammationmentioning
confidence: 99%
“…As a functional immune system is proposed to be a vital factor in the development of MRONJ, this has been an area of active investigation. Recent in vitro studies have demonstrated the reduction of macrophage viability and monocyte differentiation as well as increased matrix metalloproteinase expression in the setting of BP exposure utilizing a THP-1 human monocytic cell model 23 , 24 . Further, analyses of osseous specimens from patients diagnosed with MRONJ have also demonstrated a marked increase in both macrophage infiltration as well as polarization toward a destructive M1, or classically-activated, phenotype mediated by BP exposure which may impair bone tissue homeostasis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of macrophages is disrupted by increased MMP expression, leading to impaired wound healing in MRONJ-affected areas. 32 Through the inhibition of RANKL, denosumab may affect the expression of RANK on immune cells, such as dendritic cells, monocytes, or macrophages. RANKL increases the production of proinflammatory cytokines and reduces monocyte apoptosis.…”
Section: Infection and Immunitymentioning
confidence: 99%